TMAO as a potential biomarker and therapeutic target for chronic kidney disease: A review - Zixin, Ye; Lulu, Chen; Xiangchang, Zeng; Qing, Fang; Binjie, Zheng; Chunyang, Luo; Tai, Rao; Dongsheng, Ouyang (Frontiers in Pharmacology, 2022)
The gut microbiota and its metabolites have become a hotspot of recent research. Trimethylamine N-oxide (TMAO) metabolized by the gut microbiota is closely related to many diseases such as cardiovascular disease, chronic kidney disease, type 2 diabetes, etc. Chronic kidney disease (CKD) is an important contributor to morbidity and mortality from non-communicable diseases. Recently, increasing focus has been put on the role of TMAO in the development and progress of chronic kidney disease. The level of TMAO in patients with chronic kidney disease is significantly increased, and a high level of TMAO deteriorates chronic kidney disease. This article describes the relationship between TMAO and chronic kidney disease and the research progress of drugs targeted TMAO, providing a reference for the development of anti-chronic kidney disease drugs targeted TMAO.